Inorganic water-soluble binder system
By using adhesive compositions containing granular refractory materials, alkali metal silicates, potassium carbonate and pozzolanoic ash, the problems of insufficient strength and difficulty in removing traditional resin adhesive cores in high-pressure molding process are solved, and high efficiency is achieved. Environmentally friendly core removal and casting results.
Patent Information
- Application Number
- CN202380044396.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-06-08
- Publication Date
- 2025-01-10
AI Technical Summary
In casting or molding processes, traditional resin adhesive cores are difficult to thermally decompose in high-pressure molding processes, resulting in insufficient core strength and difficult to remove, and alternative methods such as high cost of soluble salt cores or the generation of volatile organic compound tapes Come to environmental risks.
Using adhesive compositions containing granular refractory materials, alkali metal silicates, potassium carbonate and pozzolan additives, the formed core can be dissolved in water and removed from the casting article without mechanical force, providing high strength and High quality surface finish and internal cavity cleanliness.
The effective removal of the core in the high-pressure mold casting process is achieved, the insufficient strength and environmental pollution problems in the traditional methods are avoided, and the high-strength and high-quality casting results are provided.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for use as a core in a casting or molding process, a core comprising the composition, a casting mold comprising the core, and a method for producing an article using the core. In particular, the present invention relates to a core that can be flushed out of the internal cavity of a cast or molded article using water.
[0002] background
[0003] In the gravity casting process, molten metal (or metal alloy) is poured into a pre-formed mold cavity that defines the outer shape of the casting, and the molten metal fills the mold cavity under the action of gravity. The shape of the hollow section or internal cavity in the casting can be defined by a disposable core, which is typically made of hardened resin-bonded sand. During the casting process, the extreme heat from the molten metal will thermally decompose the resin binder in the core, causing the core to crack and easily shake out of the finished casting when the molten metal has cooled and solidified. Hardened disposable resin-bonded sand cores are also commonly used in low-pressure or gravity sand casting processes and low-pressure die casting.
[0004] However, in die casting processes where the metal cools very quickly or the walls of the casting are relatively thin, the core may not be exposed to enough heat during the casting process to decompose the binder, making the core difficult to remove after the casting solidifies. Examples of such die casting processes include high pressure die casting, semi-solid casting (such as rheocasting and thixocasting), and squeeze casting. In such processes, the core will be exposed to much lower temperatures and only for a limited time, which is insufficient to thermally decompose traditional resin binders.
[0005] In conventional liquid high pressure die casting (HPDC), molten metal is injected into a mold cavity at high pressure and velocity and held in place by compressive forces until the metal solidifies. The molds used for die casting can be made of metals (such as steel) to withstand the high pressures and metal velocities and are generally reusable. In addition to extremely fast molten metal fill times, the combination of thinner casting walls and the use of active cooling systems in the tooling results in very fast solidification times.
[0006] Semi-solid casting is a variation of HPDC in which the metal (or metal alloy) is injected into the mold in a semi-solid state rather than a fully molten state, which increases kinematic viscosity and metal fluidity, allowing for even thinner wall designs, reduced porosity, and improvements in surface finish, elongation, fatigue, and tool life, among other advantages. In rheocasting, the metal is cooled from a fully molten state to a semi-solid state before injection, while in thixocasting, the solid metal is partially melted into a semi-solid state.
[0007] The use of sand cores to form internal geometries in die casting applications is desirable, but problematic. The low thermal decomposition of binders at the relatively low times and temperatures of HPDC makes post-casting sand removal more difficult. Conventional sand cores may not be strong enough to withstand the pressures and metal velocities associated in many applications and may break during such use. Therefore, conventional resin-bonded sand cores are not suitable for most high pressure die casting processes. Although alternative methods exist for forming internal cavities in HPDC, they are not highly adopted due to process complexity and / or cost.
[0008] An alternative technology is to form the core from a soluble salt. However, this technology is cost prohibitive for all but very niche applications. A further solution to the core strength and removability issues discussed above is to use molding sand or core sand and an organic polymer binder. While it is possible to achieve cores and molds with good strength and water solubility, a common problem is the generation of volatile organic compounds (VOCs) with the thermal decomposition of the organic binder, particularly in molding processes requiring long cycle times. VOCs can present risks to foundry workers and have other negative environmental impacts that can be expensive to mitigate.
[0009] Some efforts have been made to employ conventional sand core technology in HPDC applications and to some extent the required strength can be achieved to resist the forces during filling and curing. However, these cores are extremely difficult to remove through high mechanical shock loads to the part. The thin walls and weak initial casting strength of the part can lead to damage or cracking of the casting and cause the core to retain a large amount of debris in the cavity.
[0010] The present invention seeks to alleviate or ameliorate the above-mentioned problems associated with removing internal cores from cast or moulded articles, or at least provide a useful alternative. SUMMARY OF THE INVENTION
[0012] Composition
[0013] According to a first aspect of the present invention, there is provided a composition for making a core for use in a molding or metal casting process. The composition may comprise a granular refractory material. The composition may comprise a binder composition. The binder composition may comprise at least one alkali metal silicate. The binder composition may comprise potassium carbonate. The binder composition may comprise at least one pozzolanic additive.
[0014] The inventors of the present invention have found that the core made of the composition of the first aspect has enough strength to withstand the forces experienced in the casting or molding process, but can be flushed out from the internal cavity of the casting or molded product with water only. In particular, the composition does not require mechanical force to remove the core from the molded part, and provides high-quality surface finish and high-level cleanliness of the internal cavity. For the avoidance of doubt, as used herein, the term "solubility" refers to the solubility of the binder composition. About the solidified core formed by the composition, the discussion about "solubility" is intended to refer to the water dispersibility of the solidified core. It should be understood that granular refractory materials are usually insoluble.
[0015] In some embodiments, the core made using the composition is water soluble even after heating to at least 200° C. In some embodiments, the core made using the composition is water soluble after heating to a temperature of 200 to 350° C.
[0016] Relative to the weight of the granular refractory material, the binder can account for 1.5 to 35 weight %. In some embodiments, based on the weight of the granular refractory material, the composition comprises at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19 or at least 20 weight % of the binder composition. In some embodiments, based on the weight of the granular refractory material, the composition comprises no more than 35, no more than 30, no more than 25, no more than 20, no more than 15, no more than 10, no more than 5 or no more than 2 weight % of the binder composition. In some embodiments, based on the weight of the granular refractory material, the binder composition comprises 0.5 to 30, 1 to 20, 2 to 15 or 2 to 10 weight % of the binder composition.
[0017] The binder composition may be an inorganic binder composition.Such embodiments have advantages because they avoid the generation of VOCs due to combustion or pyrolysis of the binder in contact with molten metal.
[0018] Alkali metal silicates
[0019] The at least one alkali metal silicate may comprise 1 to 15 weight percent relative to the weight of the granular refractory material. The at least one alkali metal silicate may comprise at least 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, or at least 14 weight percent relative to the weight of the granular refractory material. In some embodiments, the at least one alkali metal silicate may comprise no more than 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, or 2 weight percent of the granular refractory material.
[0020] In some embodiments, the at least one alkali metal silicate comprises sodium silicate. In some embodiments, the at least one alkali metal silicate comprises potassium silicate. In one series of embodiments, the at least one alkali metal silicate comprises sodium silicate and potassium silicate.
[0021] The alkali metal silicate can be in the form of an aqueous solution. The aqueous solution can have a solid content between 30 and 50 wt %. In some embodiments, the solid content can be 32 to 48 wt %, 34 to 46 wt %, 35 to 45 wt %, 36 to 44 wt % or 38 to 42 %. The solid content can be about 40 wt %.
[0022] In some embodiments, the binder composition may further include 1 to 3 wt % water relative to the granular refractory material.
[0023] Volcanic ash additives
[0024] In the present invention, the composition comprises at least one pozzolanic additive. The pozzolanic additive is typically a fine powdered material. The at least one pozzolanic additive may account for 0.5 to 10 weight % relative to the weight of the granular refractory. In some embodiments, the at least one pozzolanic additive accounts for at least 1, 2, 3, 4, 5, 6, 7, 8 or 9 weight % relative to the weight of the granular refractory. In some embodiments, the at least one pozzolanic granular refractory accounts for no more than 9, 8, 7, 6, 5, 4, 3, 2 or 1 weight % relative to the weight of the granular refractory.
[0025] The inventors have found that small amounts of pozzolanic additives increase the strength of cores produced from the composition. More desirably, the present composition has a significantly lower proportion of pozzolanic additive than conventional binder systems.
[0026] The at least one pozzolanic additive may be selected from the group consisting of silica fume, fly ash, rice husk ash, diatomaceous earth, volcanic ash, metakaolin and mixtures thereof. The at least one pozzolanic additive may comprise spherical particles and / or hollow microspheres. In a preferred embodiment, the at least one pozzolanic additive comprises silica fume.
[0027] In some embodiments, the at least one pozzolanic additive has a D50 particle size of no greater than 20 μm, no greater than 10 μm, no greater than 5 μm, no greater than 2 μm, no greater than 1 μm, no greater than 0.5 μm, or no greater than 0.1 μm. In some embodiments, the at least one pozzolanic additive has a D50 particle size of at least 0.01 μm, at least 0.05 μm, at least 0.1 μm, or at least 0.5 μm. In some embodiments, the at least one pozzolanic additive has a D50 particle size of 0.01 μm to 50 μm, 0.01 to 20 μm, 0.01 to 10 μm, 0.01 μm to 5 μm, or 0.01 μm to 2 μm.
[0028] Potassium carbonate
[0029] Potassium carbonate may comprise 0.125 to 10 weight percent relative to the weight of the granular refractory material. In some embodiments, potassium carbonate may comprise at least 0.2, 0.3, 0.4, 0.5, 0.75, 1, 2, 3, 4, 5, 6, 7, 8, or 9 weight percent. In some embodiments, potassium carbonate may comprise no more than 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.75, 0.5, 0.4, 0.3, or 0.2 weight percent. The inventors have discovered that the addition of potassium carbonate to the composition increases the solubility of the core formed from the composition.
[0030] Surfactants
[0031] In a series of embodiments, the composition further comprises at least one surfactant. The at least one surfactant may be selected from the group consisting of anionic, cationic, nonionic and amphoteric surfactants and mixtures thereof. Surfactant types suitable for use in the present invention include sulfates, methyl sulfates, linear alcohol sulfates, sulfonates, sulfosuccinates, phosphates, glucosides and mixtures thereof. In particular, the at least one surfactant may be selected from the group consisting of the following: 2-ethylhexyl sulfosuccinate, 2-ethylhexyl sulfate, dodecylbenzene sulfonate, nonylphenol sulfate, sodium laureth sulphate, 3-ethylhexyl phosphate, undecylamidopropyl trimethyl ammonium methylsulfate, alkyl polyglycol ether ammonium methylsulfate, 2-ethylhexyl glucoside, hexyl glucoside and mixtures thereof. In a preferred embodiment, the surfactant comprises sodium ethylhexyl sulfate.
[0032] The inventors of the present invention have found that adhesive compositions with high surface tension can reduce the fluidity of the composition, and adding a small amount of surfactant can significantly improve the fluidity of the composition by reducing the surface tension of the adhesive composition. Conversely, due to the above reasons, the increased fluidity of the composition leads to a core with improved strength.
[0033] Granular refractory material
[0034] The granular refractory material may be a natural refractory material. The refractory material may be a synthetic refractory material. In some embodiments, more than one refractory material may be used.
[0035] In some embodiments, granular refractory material comprises sand. The sand can be any type of refractory sand, such as quartz sand. In some embodiments, granular refractory material can comprise any one or more conventional refractory materials, such as oxides, carbides, nitrides, etc. of silicon, aluminum, magnesium, calcium and zirconium and other elements. Suitable refractory materials include but are not limited to quartz, olivine, chromite, zircon and alumina. In some embodiments, granular refractory material comprises spherical particles and / or hollow microspheres, such as fly ash. In some embodiments, granular refractory material comprises a mixture of sand and spherical particles and / or hollow microspheres, such as a mixture of sand and fly ash.
[0036] In embodiments where both the granular refractory material and the pozzolanic additive comprise spherical particles and / or hollow microspheres, the granular refractory material and the pozzolanic additive may simultaneously comprise the same type of spherical particles and / or hollow microspheres, such as fly ash. Alternatively, the granular refractory material and the pozzolanic additive may comprise different types of spherical particles and / or hollow microspheres, for example, the granular refractory material may comprise fly ash, while the pozzolanic additive comprises silica fume. It should be understood that in embodiments where both the granular refractory material and the pozzolanic additive comprise the same type of spherical particles and / or hollow microspheres, the D50 particle size of the granular refractory material will be greater than the D50 particle size of the pozzolanic additive, such that the granular refractory material is distinguished from the pozzolanic additive.
[0037] In some embodiments, the D50 particle size of the granular refractory material is at least 20 μm, at least 50 μm, at least 100 μm, at least 250 μm, or at least 500 μm. In some embodiments, the D50 particle size of the granular refractory material is no greater than 2 mm, no greater than 1 mm, or no greater than 500 μm. In some embodiments, the D50 particle size of the granular refractory material is 20 μm to 2 mm, 50 μm to 2 mm, or 50 μm to 1 mm.
[0038] core
[0039] According to a second aspect of the present invention there is provided a core for use in a moulding or metal casting process comprising the composition of the first aspect of the present invention.
[0040] The core may be coated with a surface coating. The surface coating may be any coating suitable for refractory applications. The surface coating may comprise one or more of boron nitride, silicate, titanium dioxide, aluminum oxide, zirconium oxide, aluminum oxide, aluminum silicate or a mixture thereof. In some embodiments, the surface coating may be a sealant.
[0041] The core may be water dispersible. The core may be configured to degrade the cured core composition in water so that a cylinder of the cured core composition with a maximum height of 80 mm and a maximum diameter of 50 mm disintegrates in less than 10 minutes when immersed in water. Preferably, the cured core disintegrates in less than 5 minutes, 4 minutes, 3 minutes, 2 minutes, 1 minute, 45 seconds, 30 seconds or 15 seconds. The water may be at a temperature of 20°C. In some embodiments, the water may be at least 30, 40, 50 or 60°C. In some embodiments, the water may be less than 100°C, for example, less than 90, 80, 70, 60 or 50°C. The water may be stirred at a speed of at least 60 rpm. The water may be stirred at less than 150 rpm.
[0042] In some embodiments, the cured core composition may have a maximum load of at least 250 N / cm 2 In some embodiments, the cured core composition has a flexural strength of at least 500 N / cm 2 , at least 750 N / cm 2 or at least 1000 N / cm 2 Where possible, higher flexural strength is preferred to reduce the chance of core cracking during casting.
[0043] In some embodiments, a cylinder of the cured core composition disintegrates in water in less than 10 minutes after being heated to a temperature of 200 to 350°C.
[0044] Mould
[0045] According to a third aspect of the present invention, there is provided a mould comprising the core of the second aspect. The mould is useful for producing an article by metal casting and the core is used to define an internal cavity of the article.
[0046] The mold may be used for high pressure die casting, semi-solid casting and / or squeeze casting.
[0047] method
[0048] According to a fourth aspect of the present invention, a method for producing an article by high pressure die casting or semi-solid casting is provided. The method may include mixing the composition according to the first aspect to form a mixture. The method may include molding and hardening the mixture to produce a core, the core having the shape of an internal cavity of the article. The method may include assembling the core with a mold for high pressure die casting or semi-solid casting so that the mold and the core jointly define a casting cavity. The method may include injecting molten or semi-solid metal into the casting cavity until the cavity is filled. The method may include cooling and solidifying the molten or semi-molten metal to form the article, the core being contained in the internal cavity of the article. The method may include removing the article containing the core from the mold. The method may include removing the core from the internal cavity by flushing with water.
[0049] The method may further comprise the step of coating the core with a surface coating prior to assembling the core with the mold.
[0050] The step of molding and hardening the mixture may include drying the mixture. The step of molding and hardening the mixture may include compacting the mixture into a core mold. The step of molding and hardening the mixture may be performed using a core shooting device. The step of molding and hardening the mixture to produce a core includes producing the core by an additive manufacturing or 3D printing process.
[0051] In a further aspect of the present invention there is provided use of a composition according to the first aspect of the present invention in a moulding process or a metal casting process. Example
[0052] Example 1 - Comparative Example
[0053] Initially the following example compositions were prepared:
[0054] Table 1
[0055]
[0056]
[0057] a % by weight relative to the total weight of the adhesive composition (excluding the pozzolanic additive), b Weight % relative to the weight of the particles c Weight % relative to the total weight of pozzolanic additives d Aqueous solution, 40% w / v solids content, e Aqueous solution, 20% w / v solids content, f Aqueous solution, 35-45% w / v solids
[0058] 1 BASF GmbH, Ludwigshaven, Germany; 2 Intercol BV, Ede, The Netherlands; 3 BrenntagBV, Enschede, The Netherlands; 4 PQ Corporation BV, Eysden, The Netherlands; 5 Mercur Handel GmbH, Düsseldorf, Germany; 6 Vivochem BV. Almelo, The Netherlands; 7 AVEBE BV, Veendam, The Netherlands; 8 Foseco BV, Enschede, The Netherlands; 9 Vivochem BV, Almelo, The Netherlands; 10 Cofermin Chemicals GmbH, Essen, Germany; 11 Staus-Perlite GmbH, St. Poelten, Austria; 12 Columbian Carbon GmbH, Hannover, Germany; 13 Xatico Benelux-France SarL, Troisvierges, Luxembourg
[0059] Comparative compositions C1 to C3 are examples of compositions described in international application PCT / EP2021 / 079512. Alkali metal silicate is first mixed with water and the solution is then mixed with a mixture of pozzolanic additive, potassium carbonate and particulate matter to form composition 1. Cores are then formed using a Laempe L1 core shooter at a core shooting pressure of 4 bar and a core shooting time of 1 second and a core box temperature of 140°C. All cores are solidified with hot air (120°C) and different purge times are used depending on the size and shape of the core produced.
[0060] The adhesive solubility was evaluated by immersing the solidified core in water and spinning the solidified core at the temperature and rotation speed indicated in the table above. If the core dissolved within 5 seconds of immersion in water, regardless of its temperature, the adhesive solubility was determined to be "excellent". Cores that dispersed in water within 5 to 45 seconds were considered "good", those within 45 to 120 seconds were "fair", those within 120 seconds to 600 seconds were "poor", and >600 seconds were "insoluble".
[0061] It was found that the comparative compositions C1 and C3 had excellent flexural strength, about 800 N / cm 2 C1 also had good solubility – in tests in water at 20°C and 60 rpm rotation, the adhesive dissolved in 20-40 seconds, and in 15 seconds at 65°C and 150 rpm. C3 had good solubility, dissolving in water at 65°C and 150 rpm in 15 to 45 seconds, although solubility at 20°C and 60 rpm was poor, typically requiring 240-260 seconds.
[0062] Comparative composition C2 has a strength of about 800 N / cm 2 The adhesive composition had a comparable flexural strength of , but it was not soluble in water within 600 seconds. Therefore, it was determined to be unsuitable for use in forming a core for a molding process because it would be impossible to effectively remove the core from the mold.
[0063] The flexural strength and solubility of C1 and C3 make them useful in HPDC and other casting processes. However, to achieve the necessary strength, each requires relatively high levels of pozzolanic additives. Silica fume A is a byproduct from zirconium oxide production and is known to contain heavy metal contaminants. In particular, the presence of lead and nickel can lead to wastewater contamination during the cleaning of the molding sand in some molding processes, so additional processes are required to prevent water contamination.
[0064] Example 2 - Effect of Alkali Metal Silicate Content
[0065] The following compositions were prepared to evaluate the effect of alkali metal silicate content on core properties.
[0066] Table 2
[0067]
[0068] a H33 is quartz sand (Quarzwerke GmbH, Haltern, Germany); b Weight % relative to the weight of the particles.
[0069] The alkali metal silicate, MTR 6099 / 17, is a mixture of sodium silicate (90 wt % Crystal 230, PQ Corporation BV, Eysden, The Netherlands), potassium silicate (5.0 wt % Kasil 1841 PQ Corporation BV, Eysden, The Netherlands), water (4.5 wt %) and DSK40 (0.5 wt % Brenntag BV, Enschede, The Netherlands). Without wishing to be bound by theory, it is believed that the reduced surface tension due to the presence of the surfactant improves the flowability of the composition, thereby improving the compaction, density and mechanical strength of the resulting core.
[0070] Cores were formed according to Example 1. Tests have shown that increasing the alkali metal silicate content leads to a small increase in the flexural strength. At very high binder contents relative to the granulate, structural losses were observed. At 20% by weight of alkali metal silicate, the composition was a wet paste and core formation was not possible.
[0071] In all cases, the solubility of the core in hot tap water (about 65°C) was good and was not affected by the increase in strength resulting from increasing alkali metal silicate content.
[0072] Example 3 - Effect of K2CO3 content
[0073] The following compositions were prepared to evaluate the effect of K2CO3 content on core properties.
[0074] Table 3a
[0075]
[0076] a H33 is quartz sand (Quarzwerke GmbH, Haltern, Germany); b Weight % relative to the weight of the particles.
[0077] In the compositions shown in Table 3a, it is shown that a small amount of potassium carbonate still provides improved binder solubility over the prior art. Increasing potassium carbonate does not appear to improve the strength and solubility of the core. At the highest potassium carbonate level tested (10 wt %), the core exhibits defects. Without wishing to be bound by theory, it is believed that such defects were caused by the lower fluidity of Composition 8 due to the high potassium carbonate level, so higher levels of potassium carbonate were not tested.
[0078] Table 3b
[0079]
[0080]
[0081] a LA32 is quartz sand from Sibelco, France (AFS = 53)
[0082] b Weight % relative to the weight of the particles.
[0083] In the composition of Table 3b, in order to dissolve the potassium carbonate, an equal portion of water was added to the potassium carbonate before mixing with the alkali metal silicate, pozzolanic additive and particulate matter. Cores were formed according to Example 1.
[0084] The tests showed that the presence of potassium carbonate greatly improved the solubility of the adhesive composition, thereby improving the water dispersibility of the corresponding core formed from the composition, but as supported by Table 3a, increasing the K2CO3 level did not further improve the solubility. It was found that even low potassium carbonate levels (such as 0.5 wt%) still demonstrated improved solubility compared to compositions without potassium carbonate.
[0085] A further benefit was found to be an increase in flexural strength, even at relatively low levels of potassium carbonate. Without wishing to be bound by theory, it is thought that the presence of potassium carbonate improves the chemical bonding between individual sand grains. This effect was also observed in H33 sand (see Table 3a above) - initially the strength increased to about 3 wt%. Higher concentrations resulted in a less stable situation and lower strength values were observed.
[0086] Example 4 - Effect of pozzolanic additives
[0087] The following compositions were prepared to evaluate the effect of pozzolan content and composition on core properties.
[0088] Table 4a
[0089]
[0090] a H33 is quartz sand (Quarzwerke GmbH, Haltern, Germany); b Weight relative to the weight of the particles; d Silica fume A; e MS – Microsit MS971U (microsilica – Elkem Microsilica, Norway); f H10 – Microsit H10 fly ash (BauMineral GmbH, Herten, Germany);
[0091] The tests showed that both silica fume and microsilica had a significant positive effect on the flexural strength of the core. The fly ash was found to have a less pronounced effect on strength than the examples without pozzolanic additives, with the values being approximately the same within their respective error ranges. The sample weights of the cores without pozzolanic additives were the lowest in these tests, indicating that the cores had the worst compaction and thus the lowest density.
[0092] Table 4b
[0093]
[0094] a H33 is quartz sand (Quarzwerke GmbH, Haltern, Germany); bThe components are expressed as wt % relative to the weight of the particle; g XSW – XSW-95U (silica fume – Possehl Erzkontor GmbH, Lübeck, Germany); h SFP – Denka SFP (Silica Fume – Denka Company Limited, Tokyo, Japan); I MS ZZ – Microsilica ZZ (Moertelshop GmbH, Germany)
[0095] Compositions 16 to 18 demonstrate that the high strength achievable using silica fume and microsilica is reproducibly achieved by substituting silica fume and microsilica products and is not limited to a single supplier or product. Compositions 19 and 20 show significantly increased flexural strength with increasing pozzolanic additive content. However, increasing pozzolanic content significantly reduces the solubility of the core.
[0096] Example 5 - Effect of Refractory Granular Material
[0097] The following compositions were prepared to evaluate the effect of the type of refractory granular material on core properties.
[0098] Table 5
[0099]
[0100] a H33 is quartz sand; b The components are expressed as wt % relative to the weight of the particle; c 'Nissan' is synthetic sand - NISSAN, China, AFS 61; d Bauxite 65 - Ziegler & Co, GmbH, Germany, AFS 65; e Fosbeads – Foseco, Netherlands, AFS 52; f Poraver (Dennert Poraver GmbH, Schlüsselfeld, Germany) – Glass beads – 0.1 – 0.3 mm
[0101] These tests show that similar results can be repeated with alternative choices of granular refractory materials.Compositions 21 to 23 are synthetic sands typically used in foundry applications requiring high strength.
[0102] Without wishing to be bound by theory, it is believed that the presence of the pozzolanic additive aids in the flowability of the mixture and increases strength because the smaller particle size of the pozzolanic additive provides better packing, thereby increasing the density of the core. The synthetic sand tested was spherical, and therefore required a lower addition rate of the binder composition to achieve similar strength. The use of Poraver (small, spherical, expanded glass beads) failed to produce an effective core, which is believed to be due to the very low density. These test results indicate that synthetic sand and synthetic spherical ceramic particles can be used with the binder composition to provide an ideal core for a molding process.
[0103] Example 6 - Effects of various types of alkaline silicates
[0104] The following compositions were prepared to evaluate the effect of the type of alkali silicate on core properties.
[0105] Table 6
[0106]
[0107] a Quartz sand H33 (Quarzwerke GmbH, Haltern, Germany); 1 MTR 6099 / 17*: Foseco BV, Enschede, The Netherlands; 2 Crystal 230M = Crystal 230 + 20 wt% water + 0.5 wt% DSK40 (surfactant); 3 Kasil1841M = Kasil 1841 + 20 wt% water + 0.5 wt% DSK40 (surfactant); 4 Crystal 230M2 = Crystal 230 + 20 wt% water, without DSK40
[0108] Table 6 shows the effect of different types of alkaline silicates on the quality and water solubility of the core formed from the composition. MTR 6099 / 17*, Crystal 230M and Crystal 230M2 using sodium silicate base were found to have excellent performance. Composition 29 contained 5 parts by weight of Kasil 1841M, which contained potassium silicate, 20% by weight of water and 0.5% by weight of surfactant. The use of only potassium silicate in composition 29 resulted in a slight decrease in mechanical strength and a decrease in water solubility, but both were acceptable.
[0109] Compositions 28 and 30 differ only in the presence of a small amount of surfactant (an alkaline silicate composition comprising 0.5 wt% DSK40) in composition 28. It was found that without DSK40, the weight and mechanical strength of the core samples formed from the composition were lower. Composition 27, which contained a mixture of both sodium silicate and potassium silicate, performed well in the solubility test and provided lower viscosity and better flowability than compositions 28 and 30, which contained only sodium silicate. Without wishing to be bound by theory, it is believed that the lower viscosity and better flowability resulted in the cores formed having higher compaction and density, and thus higher flexural strength, due to the inclusion of small amounts of surfactant and potassium silicate.
[0110] Example 7 - Effect of recovered sand
[0111] The impact of recycled particulate matter was studied.
[0112] Table 7
[0113]
[0114] Composition 31 used a fresh sample of LA32 that had not been previously used as a baseline. In composition 32, the granular material LA32 had been recovered and recycled five times - each time using the same binder system. These results indicate that the use of recycled granular material does not significantly affect the weight or strength of the core formed, and therefore does not negatively affect the performance of the binder system.
[0115] Example 8 - Effect of Storage Conditions
[0116] A series of storage conditions and storage periods were studied using a series of identical cores formed from Composition 1 above. Different conditions were selected to evaluate the effects of exposure to ambient conditions or storage in sealed plastic bags. The sample cores all had an initial sample weight of 426.1 g and an initial flexural strength of 1009 ± 50 N / cm 2 .
[0117] Table 8a
[0118]
[0119] a H33 is quartz sand (AFS 53) (Quarzwerke GmbH, Haltern, Germany); b Weight % relative to the weight of the particles
[0120] Exposure tests were conducted for up to one week (168 hours) with the cores stored at 25°C and 30% relative humidity (RH) (consistent with maximum storage times and typical conditions at a foundry). Another batch (Example E38) was stored in sealed plastic bags. Water solubility was determined using hot tap water (65°C). In all tests, the solubility of the cores was found to be good, indicating that the desired solubility characteristics were maintained over the life of the product in use.
[0121] The experiment was then repeated with a composition comprising 7 wt% alkali metal silicate and 1.5 wt% potassium carbonate relative to the weight of the granules. The initial sample weight was 419.2 g and the initial flexural strength was 950 ± 23 N / cm 2 The results are shown in Table 8b.
[0122] Table 8b
[0123]
[0124]
[0125] a H33 is quartz sand (AFS 53) (Quarzwerke GmbH, Haltern, Germany); b Weight % relative to the weight of the particles
[0126] These tests show that regardless of the amount of potassium carbonate or storage conditions, the water solubility of the produced cores remains acceptable at a maximum storage period of 168 hours. In all cases, the sand cores with 3.0 wt. % potassium carbonate show slightly higher water solubility rates. All tests were conducted using hot tap water (65° C.).
Claims
1. A composition for making a core for use in a molding or metal casting process, the composition comprising: Granular refractory materials; and An adhesive composition, comprising: 1 to 15% by weight of at least one alkali metal silicate: 0.125 to 10 wt % potassium carbonate; and 0.5 to 10% by weight of at least one pozzolanic additive, The range of the binder composition is relative to the weight of the granular refractory material.
2. The composition according to claim 1, wherein the binder accounts for 1.5 to 35% by weight relative to the weight of the granular refractory material.
3. A composition according to any preceding claim, wherein the binder composition is an inorganic binder composition.
4. The composition according to any preceding claim, wherein the at least one alkali metal silicate comprises sodium silicate and potassium silicate.
5. A composition according to any preceding claim, wherein the at least one alkali metal silicate is in the form of an aqueous solution and has a solids content of between 30 and 50% by weight.
6. A composition according to any preceding claim, wherein the at least one pozzolanic additive has a D50 particle size of no greater than 20 μm.
7. A composition according to any preceding claim, wherein the at least one pozzolanic additive comprises silica fume.
8. A composition according to any preceding claim, wherein the potassium carbonate comprises 1 to 6 wt% relative to the weight of the granular refractory material.
9. A composition according to any preceding claim further comprising a surfactant, and optionally wherein the surfactant is sodium ethylhexyl sulfate.
10. A composition according to any preceding claim, wherein the binder composition further comprises 1-3 wt% water relative to the weight of the granular refractory material.
11. A core for use in a moulding or metal casting process, the core comprising a composition according to any one of the preceding claims.
12. The core of claim 11, wherein the core is coated with a surface coating, and optionally wherein the surface coating comprises boron nitride, a silicate, titanium dioxide, aluminum oxide, zirconium oxide, aluminum oxide, aluminum silicate, or a mixture thereof.
13. A mould comprising a core according to claim 11 or 12, wherein the mould is for producing an article by metal casting and the core is for defining an internal cavity of the article.
14. A method for producing an article by high pressure die casting or semi-solid casting, the method comprising the steps of: (i) mixing the composition according to any one of claims 1 to 10 to form a mixture; (ii) moulding and hardening the mixture to produce a core having the shape of the interior cavity of the article; (iii) assembling the core with a mold for high pressure die casting or semi-solid casting, such that the mold and the core together define a casting cavity; (iv) injecting molten or semi-solid metal into the casting cavity until the cavity is filled; (v) cooling and solidifying the molten or semi-molten metal to form the article, the core being received within the interior cavity of the article; (vi) removing the article containing the core from the mold; and (vii) removing the core from the interior cavity by flushing with water.
15. Use of the composition according to any one of claims 1 to 10 in a molding process or a metal casting process.